2021
DOI: 10.1101/2021.09.27.461930
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Milk casein prevents inactivation effect of black tea galloylated theaflavins on SARS-CoV-2 in vitro

Abstract: Repeated emergence of highly contagious and potentially immune-evading variant SARS-CoV-2 is posing global health and socioeconomical threats. For suppression of the spread of the virus infection among people, a procedure to inactivate virus in saliva may be useful, because saliva of infected persons is the major origin of droplets and aerosols that mediate viral transmission to nearby persons. We previously reported that SARS-CoV-2 is rapidly and remarkably inactivated by treatment in vitro with tea including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…We also found that the tea catechin compound (−)-epigallocatechin gallate (EGCG) powerfully and rapidly inactivated the virus [16][17][18] , which was also reported by other groups [19][20][21] . Similar effects were also seen in black tea ingredients, galloylated theaflavins (theaflavin-3-O-gallate (TF3G), theaflavin-3'-O-gallate (TF3'G), and theaflavin-3,3'-Odigallate (TFDG)), and theasinensin A (TSA) that are derivatives of tea catechins 17,22 . We also reported that the EGCG, TFDG and TSA interfered with the interaction between viral spike protein and ACE2 by binding to the spike protein receptor binding domain (RBD).…”
mentioning
confidence: 63%
“…We also found that the tea catechin compound (−)-epigallocatechin gallate (EGCG) powerfully and rapidly inactivated the virus [16][17][18] , which was also reported by other groups [19][20][21] . Similar effects were also seen in black tea ingredients, galloylated theaflavins (theaflavin-3-O-gallate (TF3G), theaflavin-3'-O-gallate (TF3'G), and theaflavin-3,3'-Odigallate (TFDG)), and theasinensin A (TSA) that are derivatives of tea catechins 17,22 . We also reported that the EGCG, TFDG and TSA interfered with the interaction between viral spike protein and ACE2 by binding to the spike protein receptor binding domain (RBD).…”
mentioning
confidence: 63%